Frequency of Celiac Disease in Patient Presenting with Iron Deficiency Anemia Referred For Endoscopic Evaluation in a Tertiary Care Hospitals (Medical Forum Monthly, 2024)
Objective: To determine the prevalence of celiac disease among patients referred for endoscopic assessment at a tertiary care hospital for the treatment of iron deficient anemia.Study Design: Cross-sectional studyPlace and Duration of Study: This study was conducted at the Department of Gastroenterology, Lahore general Hospital, Lahore during the time period from 7-2-2019 to 7-8-2019.Methods: The 205 patients that were enrolled all met the inclusion criteria. A blood sample was drawn for anti-tTG level. If >15IU/ml, then patient sent for upper gastrointestinal endoscopy and duodenal biopsies and if they are significant for celiac disease, it was labeled. All data was analyzed in SPSS version 21.Results: In this study the mean age of the patients was 40.85±13.10 years, male to female ratio of the patients was 0.79:1. The mean value of anti tTG of the patients was 14.66±9.11 u/ml. Among IDA patients the celiac disease found in 27(13.17%) patients.Conclusion: According to this study the frequency of celiac disease is 13.2% in patient presenting with IDA who were referred for endoscopic evaluation.